Design of a Web-Based Report Card and Academic Agenda Information System using the Agile Methode at SD Negeri 067260 Medan - Rizky Ardiyanti; Herman; Hoki, Leony (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
A school is a system made up of elements that are interconnected and influence each other to achieve a single goal. The processing of school academic data carried out manually is ineffective because there are still many errors. This research aims to help improve the efficiency of academic data management, the accessibility and accuracy of academic information, as well as the participation of students and teachers in academic data management at SD Negeri 067260 Medan. In this study, the author designed a website-based report card and academic agenda information system using agile methods consisting of planning, design, coding, and testing. The results of this research are a website-based report card information system and academic agenda.